Factors Associated With the Intention to Participate in Coronavirus Disease 2019 Frontline Prevention Activities Among Nursing Students in Vietnam: An Application of the Theory of Planned Behavior - Tran, Quynh Anh; Nguyen, Huong Thi Thanh; Bui, Tung Van; Tran, Nguyet Thi; Nguyen, Nguyet Thi; Nguyen, Tham Thi; Nguyen, Hien Thu; Nguyen, Son Hoang (Frontiers in Public Health, 2021)
Introduction: Medical students have been serving as a key part of the front-line health workforce responding to the COVID-19 pandemic globally. Their contribution is especially important in resource-scarce setting of developing nations such as Vietnam. Yet, the intention of medical students, in particular nursing students to participate in COVID-19 frontline prevention activities has not been well understood. This paper aimed to examine factors associated with the intention to participate in COVID-19 frontline prevention activities among Vietnamese nursing students. Method: A cross-sectional study was conducted on a total of 597 students in December 2020 in Hanoi, Vietnam. Information regarding the socio-economic characteristics of participants, their source of COVID-19 related knowledge, perception and attitude towards participating in COVID-19 frontline activities (based on Theory of Planned Behaviour) was collected. Hierarchical regression model was employed to examine the association between students’ intention and associated factors. Results: A positive intention to participate in COVID-19 frontline prevention activities was found (mean score of 25.3 over 35; SD = 4.4; min = 5; max = 35). Attitude toward behaviour, subjective norms, and perceived behavioural control was found to significantly associated with students’ intention. These variables explained 37% of variation of the students’ intention in the model. Among three factors, subjective norm showed a strongest correlation with students’ intention ( = 0,358; p<0,001). Obtaining information from official sources and community was also found to be positively correlated with intention to participate. Conclusion: Most of the respondents reported a positive intention to participate in COVID-19 frontline prevention activities. The findings suggested that the Theory of Planned Behaviour was a good instrument to predict the intention to perform behaviour among Vietnamese students. Enhancing students’ positive attitude, encouraging family and community’s supports, and providing adequately essential resources will contribute to optimize the participation of students to confront COVID-19.